Morphological and radiological study of lymph nodes in dromedaries in Algeria - Rahmoun, D. E.; Lieshchova, M. A.; Fares, M. A. (Regulatory Mechanisms in Biosystems, 2020)
Despite significant progress in the study of the subtle mechanisms of interaction between cellular and molecular elements in immune responses, the general structure of the organs of the immune system, including the lymph node, has not been sufficiently studied, in particular in large farm animals. The lymph nodes of sexually mature camels have been studied anatomically and morphologically and advanced studies conducted using an X-ray system and a computer densitometer scanner with injection of a contrast medium. The topography and characteristics of the morphometric parameters (absolute and relative mass, linear measurements, volume) of certain somatic and visceral lymph nodes were determined. The mass of the lymph nodes studied varies according to the location and the interest of the organ in the satellite defense of the lymphoid system, For part of the x-ray examination of the lymph nodes, organs of large inguinal and axillary shape were selected after passing through a solution of tetraethyl-4,4-diamino-triphenylmethane oxalate, the lymph vessels were dilated and darkened, then iodine injections were made into the afferent lymphatic vessel of two lymph nodes; they were placed on the radiological cassette, a photograph taken on conventional radiography, for computer densitometer, the examination was made without preparation of the organs. A capsule encompasses the parenchyma of the lymph node, whose internal structure is composed of different zones, cortical, paracortical and medullary, on the one hand the lymphatic vessels were very clear especially with the conventional radiography with preparation of the organs, while the computer densitometer clearly revealed the deep texture of the parenchyma, basing it on the intensity of emission saturation from the use of computer densitometer.